(untitled) (European Journal of Formal Sciences and Engineering, 2025)
It has been a long time that human is interested in learning how to control involuntary actions such as heartbeat, blood pressure, breathing, etc., so a lot of research has been done on this issue so far. One of the methods using in this field is biofeedback, in which someone can roughly control an involuntary action or having better control over some voluntary actions such as muscle contraction through some visual or audio feedback from those actions. This study is to design and development of one biofeedback instrument, which is GSR (Galvanic Skin Response), and examine some signals that have been taken by this device.